Pengembangan Website Berbasis Konten untuk Mengatasi Distraksi Belajar dari Media Sosial Tiktok di Dusun Cuping Kabupaten Lamongan - Ahmad Iqbal Zuhdi; Andri Susanto; Priska Wulan Ndari (Universitas Palangka Raya, 2026)
This research the development of a content-based website to overcome learning distractions from TikTok social media in Cuping Hamlet, Lamongan Regency. The purpose of this study was to determine the effect of TikTok social media on children's learning interest and to develop a content-based website to address learning distractions from TikTok social media in Cuping Hamlet, Lamongan Regency. The method used was a quantitative method with a questionnaire technique distributed to 30 parents of children aged 6-12 years. The results showed a significance level of <0.05, indicating a significant negative effect between TikTok social media use and children's learning interest. Furthermore, the relationship between TikTok social media and learning interest was strong and in the opposite direction, with a correlation coefficient of -0.60.. This can be interpreted that the higher the level of TikTok social media use, the lower the child's interest in learning and vice versa. Furthermore, a content-based website has been successfully developed to address learning distractions from TikTok social media. The website development used Wix which contains the home page, about, research, publications, posts (interesting learning materials and videos), and contact.